Classification of Social Anxiety Disorder With Support Vector Machine Analysis Using Neural Correlates of Social Signals of Threat - Xing, Mengqi; Fitzgerald, Jacklynn M.; Klumpp, Heide (Frontiers in Psychiatry, 2020)
Threatening faces are potent cues in social anxiety disorder (SAD), therefore, neural response to threatening faces, particularly regions in the ‘fear’ circuit such as amygdala, may classify individuals with SAD. Previous studies of indirect/implicit processing of threatening faces have shown support vector machine (SVM) pattern recognition significantly differentiates individuals with SAD from healthy participants though evidence for the role of the fear circuit in classification has been inconsistent. We extend this literature by using SVM during direct face processing. Individuals with SAD (n=47) and healthy controls (n=46) completed a validated emotional face matching task during functional MRI which included a matching shapes control condition. SVM was based on brain response to threat (vs. happy) faces, threat faces (vs. shapes), and threat/happy faces (vs. shapes) in 90 regions encompassing frontal, limbic, parietal, temporal, and occipital systems. Recursive feature elimination (RFE) was used for feature selection and to rank the contribution of regions in predicting SAD diagnosis. SVM results for threat (vs. happy) faces revealed satisfactory accuracy (e.g., Area Under the Curve=0.72); results with shapes as ‘baseline’ yielded less optimal classification. RFE for threat (vs. happy) indicated all 90 brain regions were necessary for classification. RFE-based ranking suggested diffuse neurofunctional activation to threat (vs. happy) faces in classification. When using an RFE cut-point, regions implicated in sensory and goal-directed processes contributed relatively more in differentiating SAD from controls than other regions. Results suggest neural activity across large-scale systems, as opposed to fear circuitry alone, may aid in the diagnosis of SAD.